Crystal engineering and ferroelectricity at the nanoscale in epitaxial 1D manganese oxide on silicon. Issue 21 (13th May 2021) - Gomez, Andrés; Vila-Fungueiriño, José Manuel; Jolly, Claire; Garcia-Bermejo, Ricardo; Oró-Solé, Judith; Ferain, Etienne; Mestres, Narcís; Magén, César; Gazquez, Jaume; Rodriguez-Carvajal, Juan; Carretero-Genevrier, Adrián
Abstract : A simple chemical method is developed to integrate a novel room-temperature ferroelectric Sr1+ δ Mn8 O16 hollandite-like oxide nanowire thin film in silicon technology. This original material shows a piezoelectric coefficient d 33 value of 22 ± 6 pC N −1 . Abstract : Ferroelectric oxides have attracted much attention due to their wide range of applications, particularly in electronic devices such as nonvolatile memories and tunnel junctions. As a result, the monolithic integration of these materials into silicon technology and their nanostructuration to develop alternative cost-effective processes are among the central points in the current technology. In this work, we used a chemical route to obtain nanowire thin films of a novel Sr1+ δ Mn8 O16 (SMO) hollandite-type manganese oxide on silicon. Scanning transmission electron microscopy combined with crystallographic computing reveals a crystal structure comprising hollandite and pyrolusite units sharing the edges of their MnO6 octahedra, resulting in three types of tunnels arranged along the c axis, where the ordering of the Sr atoms produces natural symmetry breaking. The novel structure gives rise to ferroelectricity and piezoelectricity, as revealed by local direct piezoelectric force microscopy measurements, which confirmed the ferroelectric nature of the SMO nanowire thin films at room temperature and showed a piezoelectric coefficient d 33 value of 22 ± 6 pC N −1 . Moreover, we proved that flexible vertical SMO nanowires can be harvested providing an electrical output energy through the piezoelectric effect, showing excellent deformability and high interface recombination. This work indicates the possibility of engineering the integration of 1D manganese oxides on silicon, a step which precedes the production of microelectronic devices.